Dampak Dari Pembelajaran Pendidikan Agama Islam Terhadap Peserta Didik Tunanetra Total Dengan Perasaan Rendah Diri (Self-Esteem) di SLB Kartini Batam dengan Siswa AN - Kodir, Abdul (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
Islamic Religious Education (PAI) has an important role in shaping the spiritual and moral character of students, including those with special needs, such as the blind. The value of totality encourages students to give full dedication in carrying out worship and daily activities despite facing physical limitations. Meanwhile, the value of low self-esteem teaches awareness of the greatness of Allah and encourages an attitude of not being arrogant and empathetic towards others. Thus, PAI not only builds spiritual intelligence, but also forms a noble character that is adaptive to various life challenges. The research method used in this study is a Literature Review and case study. The literature review aims to provide a theoretical basis and clarify the position of the research in a broader scientific context. A case study is a learning or research method that uses real or hypothetical cases to analyze, understand, or provide solutions to a problem. The results found that Islamic Religious Education teachers in handling AN case-studies are: Recognizing feelings of inferiority and understanding their origins are important initial steps for AN. Focus on AN's strengths and achievements rather than AN's weaknesses. Focus on things that have been achieved and your strengths. Achieve simple things to build self-confidence. Maintain physical, mental, and emotional health. Whether it is in classroom learning, or learning outside the classroom which is a behavioral reinforcement program (moral education).